Motivation States for Physical Activity and Sedentary Behavior: Desire, Urge, Wanting, and Craving. - Stults-Kolehmainen, Matthew A; Blacutt, Miguel; Bartholomew, John B; Gilson, Todd A; Ash, Garrett I; McKee, Paul C; Sinha, Rajita (Frontiers in psychology, 2020)
To better explain daily fluctuations in physical activity and sedentary behavior, investigations of motivation are turning from social cognitive frameworks to those centered on affect, emotion and automaticity, such as the Affect and Health Behavior Framework (AHBF), Integrated Framework and Affective-Reflective Theory (ART). This shift has necessitated: (a) re-examination of older theories and their constructs, such as drives, needs and tensions and (b) an inspection of competing theories from other fields that also attempt to explain dynamic changes in health behaviors. The Dynamical Model of Desire, Elaborated Intrusion Theory and others commonly share with AHBF the idea that human behavior is driven strongly by desires and/or the similar concepts of wants, urges, and cravings. These affectively-charged motivation states (ACMS) change quickly and may better explain physical activity behavior from one moment to the next. Desires for movement predominantly derive from negative but also positive reinforcement. Data from clinical populations with movement dysfunction or psychiatric disorders provides further evidence of these drivers of movement. Those with Restless Legs Syndrome, akathisia, tic disorders and exercise dependence all report strong urges to move and relief when it is accomplished. Motor control research has identified centers of the brain responsible for wants and urges for muscular movement. Models elaborated herein differentiate between wants, desires, urges and cravings. The WANT model (Wants and Aversions for Neuromuscular Tasks) conceptualizes desires for movement and rest as varying by magnitude, approach or avoidance-orientation (wants versus aversions) and as occupying independent dimensions instead of opposite ends of the same axis. For instance, one hypothetically might be in a state of both high desire for movement and rest simultaneously. Variations in motivation states to move and rest may also be associated with various stress states, like freezing or fight and flight. The first validated instrument to measure feelings of desire/want for movement and rest, the CRAVE Scale (Cravings for Rest and Volitional Energy Expenditure) is already shedding light on the nature of these states. With these advances in theory, conceptual modeling and instrumentation, future investigations may explore the effects of desires and urges for movement and sedentary behavior in earnest. Copyright © 2020 Stults-Kolehmainen, Blacutt, Bartholomew, Gilson, Ash, McKee and Sinha.
15 citations (Crossref) [2023-10-31] Place: Switzerland Stults-Kolehmainen, Matthew A. Bariatric and Minimally Invasive Surgery Program, Yale-New Haven Hospital, New Haven, CT, United States. Stults-Kolehmainen, Matthew A. Department of Biobehavioral Sciences, Teachers College, Columbia University, New York, NY, United States. Blacutt, Miguel. Department of Biobehavioral Sciences, Teachers College, Columbia University, New York, NY, United States. Bartholomew, John B. Department of Kinesiology and Health Education, The University of Texas at Austin, Austin, TX, United States. Gilson, Todd A. Department of Kinesiology and Physical Education, Northern Illinois University, DeKalb, IL, United States. Ash, Garrett I. Pain Research, Informatics, Multi-morbidities, and Education (PRIME), VA Connecticut Healthcare System, West Haven, CT, United States. Ash, Garrett I. Center for Medical Informatics, Yale School of Medicine, New Haven, CT, United States. McKee, Paul C. Department of Psychology, Southern Connecticut State University, New Haven, CT, United States. Sinha, Rajita. Yale Stress Center, Yale School of Medicine, New Haven, CT, United States.
Keywords: conceptual analysis; dept.psy; desire; exercise; motivation; motivation states; peer-reviewed; physical activity; sedentary activity; urge for movement

Motivation states to move, be physically active and sedentary vary like circadian rhythms and are associated with affect and arousal - Budnick, Christopher J.; Stults-Kolehmainen, Matthew; Dadina, Cyrus; Bartholomew, John B.; Boullosa, Daniel; Ash, Garret I.; Sinha, Rajita; Blacutt, Miguel; Haughton, Adrian; Lu, Tom (Frontiers in Sports and Active Living, 2023)
IntroductionMotivation to be physically active and sedentary is a transient state that varies in response to previous behavior. It is not known: (a) if motivational states vary from morning to evening, (b) if they are related to feeling states (arousal/hedonic tone), and (c) whether they predict current behavior and intentions. The primary purpose of this study was to determine if motivation states vary across the day and in what pattern. Thirty adults from the United States were recruited from Amazon MTurk.MethodsParticipants completed 6 identical online surveys each day for 8 days beginning after waking and every 2–3 h thereafter until bedtime. Participants completed: (a) the CRAVE scale (Right now version) to measure motivation states for Move and Rest, (b) Feeling Scale, (c) Felt Arousal Scale, and (d) surveys about current movement behavior (e.g., currently sitting, standing, laying down) and intentions for exercise and sleep. Of these, 21 participants (mean age 37.7 y; 52.4% female) had complete and valid data.ResultsVisual inspection of data determined that: a) motivation states varied widely across the day, and b) most participants had a single wave cycle each day. Hierarchical linear modelling revealed that there were significant linear and quadratic time trends for both Move and Rest. Move peaked near 1500 h when Rest was at its nadir. Cosinor analysis determined that the functional waveform was circadian for Move for 81% of participants and 62% for Rest. Pleasure/displeasure and arousal independently predicted motivation states (all p's < .001), but arousal had an association twice as large. Eating, exercise and sleep behaviors, especially those over 2 h before assessment, predicted current motivation states. Move-motivation predicted current body position (e.g., laying down, sitting, walking) and intentions for exercise and sleep more consistently than rest, with the strongest prediction of behaviors planned for the next 30 min.DiscussionWhile these data must be replicated with a larger sample, results suggest that motivation states to be active or sedentary have a circadian waveform for most people and influence future behavioral intentions. These novel results highlight the need to rethink the traditional approaches typically utilized to increase physical activity levels.
2 citations (Crossref) [2023-10-31]
Keywords: dept.psy; peer-reviewed

College community–based physical activity support at a public university during the COVID-19 pandemic: retrospective longitudinal analysis of intra- versus interpersonal components for uptake and outcome association - Ash, Garrett; Mak, Selene; Haughton, Adrian; Augustine, Madilyn; Bodurtha, Phillip; Axtell, Robert; Borsari, Beatrice; Liu, Jason; Lou, Shaoke; Xin, Xin; Fucito, Lisa; Jeon, Sangchoon; et al. (JMIR mhealth and uhealth, 2025)
Background College students are vulnerable to setting long-term trajectories of low physical activity (PA) but are reachable via mobile health fitness tracking (eg, mobile health step counting) and interpersonal support tailored to the college community. However, no studies have statistically isolated the appeal and influence of these intra- and interpersonal components in college-based PA interventions. Objective This study retrospectively examined a college-based PA promotion program at a northeast US public university during the COVID-19 pandemic to (1) test the impact of student status on the use of intervention components and (2) determine whether such use was associated with successful retention and goal achievement in the program. Methods The university used a commercial platform for a 30-day PA promotion program during April 2021 with intrapersonal (step-tracker syncing, education, self-monitoring, and motivational messaging) and interpersonal (friend interactions and team games) components. App use was operationalized as intrapersonal (frequency of opening app, education, and self-monitoring) and interpersonal (friends made in-app and team affiliation and size). Results Campus-wide emails elicited sign-up by 156 undergraduate students, 57 graduate students, and 126 faculty and staff members. Objective 1 yielded the following results: undergraduates used the app less frequently (median 0.8, IQR 0.4-1.7 times per day) than other groups (graduate students: median 1.4, IQR 0.7-2.7 times per day; P=.01; faculty: median 1.3, IQR 0.7-2.7 times per day, H2=14.5; P=.001) but made the same number of friends (median 1-2) and teammates (median 8-9; P=.77 for friends and P=.93 for teammates). Objective 2 yielded the following results: most participants (313/335, 93.4%; 95% CI 90%-96%) were retained for the first 7 days, but by 30 days, retention dropped, most notably for undergraduate students (82/154, 53.2%; 95% CI 45%-61%), followed by graduate students (39/56, 70%; 95% CI 56%-81%) and faculty and staff (93/125, 74.4%; 95% CI 66%-82%; χ22=12.6; P<.001). Retention was associated with app engagement frequency (model hazard ratio 0.56, 95% CI 0.43-0.72; P<.001) and affiliation with a team having high median app engagement and a large size (intracluster correlation coefficient 0.064, 95% CI 0.001-0.164, P=.05). Meeting a daily step goal was associated with app engagement frequency (β=.72, SE=0.21; P=.001), number of friends (β=.40, SE 0.20; P=.04), and an initial motive of maintaining or increasing (rather than starting) PA (β=.99, SE=0.21; P<.001). Conclusions College students, compared with faculty and staff, used the app less frequently, used the app for a shorter duration before abandonment, and met the step goal on fewer days. Engagement with the program was associated with longer retention and better PA outcomes, which were critically modified by the interpersonal engagement. These findings suggest that college students using virtual PA support during times of physical isolation could benefit from more tailored implementation strategies (eg, timed prompts and team reassignments).
Keywords: Computer science; Coronavirus disease 2019 (COVID-19); Demography; Disease; Gerontology; Infectious disease (medical specialty); Internal medicine; Medicine; Preprint; Sociology; dept.hms

Qualitative and quantitative evidence of motivation states for physical activity, exercise and being sedentary from university student focus groups - Stults-Kolehmainen, Matthew A.; Gilson, Todd A.; SantaBarbara, Nicholas; McKee, Paul C.; Sinha, Rajita; Bartholomew, John B.; Boullosa, Daniel; Budnick, Christopher J.; Bueno, Fabio Amador; Haughton, Adrian; Barker, Jessica L.; Ash, Garrett I. (Frontiers in Sports and Active Living, 2023)
Motivation for physical activity and sedentary behaviors (e.g., desires, urges, wants, cravings) varies from moment to moment. According to the WANT model, these motivation states may be affectively-charged (e.g., felt as tension), particularly after periods of maximal exercise or extended rest. The purpose of this study was to examine postulates of the WANT model utilizing a mixed-methods approach. We hypothesized that: (1) qualitative evidence would emerge from interviews to support this model, and (2) motivation states would quantitatively change over the course of an interview period. Seventeen undergraduate students (mean age = 18.6y, 13 women) engaged in focus groups where 12 structured questions were presented. Participants completed the “right now” version of the CRAVE scale before and after interviews. Qualitative data were analyzed with content analysis. A total of 410 unique lower-order themes were classified and grouped into 43 higher order themes (HOTs). From HOTs, six super higher order themes (SHOTs) were designated: (1) wants and aversions, (2) change and stability, (3) autonomy and automaticity, (4) objectives and impulses, (5) restraining and propelling forces, and (6) stress and boredom. Participants stated that they experienced desires to move and rest, including during the interview, but these states changed rapidly and varied both randomly as well as systematically across periods of minutes to months. Some also described a total absence of desire or even aversion to move and rest. Of note, strong urges and cravings for movement, typically from conditions of deprivation (e.g., sudden withdrawal from exercise training) were associated with physical and mental manifestations, such as fidgeting and feeling restless. Urges were often consummated with behavior (e.g., exercise sessions, naps), which commonly resulted in satiation and subsequent drop in desire. Importantly, stress was frequently described as both an inhibitor and instigator of motivation states. CRAVE-Move increased pre-to-post interviews (p < .01). CRAVE-Rest demonstrated a trend to decline (p = .057). Overall, qualitative and quantitative data largely corroborated postulates of the WANT model, demonstrating that people experience wants and cravings to move and rest, and that these states appear to fluctuate significantly, especially in the context of stress, boredom, satiety, and deprivation.
2 citations (Crossref) [2023-10-31]
Keywords: dept.psy; peer-reviewed

Testing multiple delivery methods of the virtual exercise games for youth with T1D peer intervention: protocol development and feasibility - Ash, Garrett; Nam, Soohyun; Mak, Selene; Stults-Kolehmainen, Matthew; Haughton, Adrian; Turek, Carolyn; Baker, Julien; Hieftje, Kimberly; Marks, Asher; Chmielewski, Annette; Shelver, Michael; Considine, Elizabeth; et al. (Hormone Research in Paediatrics, 2026)
INTRODUCTION: Adolescents with type 1 diabetes (T1D) face barriers to moderate-to-vigorous physical activity (MVPA) such as uncertainty with self-management, limited access to supportive environments, and stigma related to living with diabetes. Opportunities for peer activities with T1D role model support are limited. To address this need, we tested iterative refinements of pilot Virtual Exercise Games for Youth with T1D (ExerT1D) for feasibility and acceptability. METHODS: The program included 6 versions: study 1 (1.1-1.4) included an active video game, and study 2 (2.1-2.2) included a virtual reality (VR) active video game. All versions included T1D exercise management education by clinicians and goal-setting guided by young adult coaches with T1D. RESULTS: Seventeen adolescents (median age 15.4 [IQR 14.6-16.4] years, 7 non-Hispanic white, 8 male, median HbA1c 8.1% [IQR 7.4%-11.1%]) were enrolled. Participants rated the program, comfort, clinicians, coaches, and group cohesion high/very high. Motivation for the video game was high. Building T1D and MVPA self-management skills was rated excellent at most sessions, as were peer interactions and enriched communication after adding immersive VR in study 2. Transitions between VR apps caused delays of 19 ± 6 min per 60 min-90 min session. Compared to baseline, HbA1c or glucose management indicator decreased over time in an exploratory analysis (d = -1.12, 90% CI: [-1.78, -0.48]). CONCLUSIONS: In a small cohort, the ExerT1D program facilitated a supportive environment for engaging diverse youth with T1D in an MVPA program led by T1D coaches. Larger studies are needed to assess the intervention's impact on engagement with physical activity, glycemic outcomes, and quality of life.
Keywords: Glycemic; Physical activity; Program evaluation; Protocol (science); Quality (philosophy); Quality of life (healthcare); dept.hms

Establishing a global standard for wearable devices in sport and fitness: Perspectives from the new england chapter of the american college of sports medicine members. - Ash, Garrett I.; Stults-Kolehmainen, Matthew A.; Busa, Michael A.; Gregory, Robert; Garber, Carol Ewing; Liu, Jason; Gerstein, Mark; Casajús, José A.; González-Agüero, A.; Constantinou, Demitri; Geistlinger, Michael; Guppy, Fergus M.; et al. (Current sports medicine reports, 2020)
The recent explosion of wearable technology and the associated concerns prompted the International Federation of Sports Medicine (FIMS) to create a quality assurance standard for wearable devices, which provides commissioned testing of marketing claims and endorsement of commercial wearables that test favorably. An open forum as announced in the conference advertising was held at the Annual Meeting of the New England Regional Chapter of the American College of Sports Medicine (NEACSM) November 7 to 8, 2019, in Providence, Rhode Island, USA for attending NEACSM members to voice their input on the process. Herein, we report the proceedings. The round table participants perceived the quality assurance standard to be important, but identified some practical process challenges that included the broad scope and complexity of the device universe, the need for a multiphase testing pathway, and the associated fees for product evaluation. The participants also supported the evaluation of device data analysis, behavioral influences, and user experience in the overall evaluation. Looking forward, the FIMS quality assurance standard faces the challenge of balancing these broader perspectives with practical constraints of budget, facilities, time, and human resources. © 2020 by the American College of Sports Medicine.
14 citations (Crossref) [2023-10-31] tex.ids: ashEstablishingGlobalStandard2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85079081076 type: Article
Keywords: Fitness Trackers; Humans; New England; Sports; Sports Medicine; United States; Wearable Electronic Devices; activity tracker; adult; article; budget; cosmos; data analysis; dept.hms; electronic device; human; peer-reviewed; quality control; sport; sports medicine

Measurement of Motivation States for Physical Activity and Sedentary Behavior: Development and Validation of the CRAVE Scale. - Stults-Kolehmainen, Matthew A; Blacutt, Miguel; Fogelman, Nia; Gilson, Todd A; Stanforth, Philip R; Divin, Amanda L; Bartholomew, John B; Filgueiras, Alberto; McKee, Paul C; Ash, Garrett I; Ciccolo, Joseph T; Brotnow Decker, Line; et al. (Frontiers in psychology, 2021)
Physical activity, and likely the motivation for it, varies throughout the day. The aim of this investigation was to create a short assessment (CRAVE: Cravings for Rest and Volitional Energy Expenditure) to measure motivation states (wants, desires, urges) for physical activity and sedentary behaviors. Five studies were conducted to develop and evaluate the construct validity and reliability of the scale, with 1,035 participants completing the scale a total of 1,697 times. In Study 1, 402 university students completed a questionnaire inquiring about the want or desire to perform behaviors "at the present moment (right now). " Items related to physical activity (e.g., "move my body") and sedentary behaviors (e.g., "do nothing active"). An exploratory structural equation model (ESEM) revealed that 10 items should be retained, loading onto two factors (5 each for Move and Rest). In Study 2, an independent sample (n = 444) confirmed these results and found that Move and Rest desires were associated with stage-of-change for exercise behavior. In Study 3, 127 community-residing participants completed the CRAVE at 6-month intervals over two years- two times each session. Across-session interclass correlations (ICC) for Move (ICC = 0.72-0.95) and Rest (ICC = 0.69-0.88) were higher than when they were measured across 24-months (Move: ICC = 0.53; Rest: ICC = 0.49), indicating wants/desires have state-like qualities. In Study 4, a maximal treadmill test was completed by 21 university students. The CRAVE was completed immediately pre and post. Move desires decreased 26% and Rest increased 74%. Changes in Move and Rest desires were moderately associated with changes in perceived physical fatigue and energy. In Study 5, 41 university students sat quietly during a 50-min lecture. They completed the CRAVE at 3 time points. Move increased 19.6% and Rest decreased 16.7%. Small correlations were detected between move and both perceived energy and tiredness, but not calmness or tension. In conclusion, the CRAVE scale has good psychometric properties. These data also support tenets of the WANT model of motivation states for movement and rest (Stults-Kolehmainen et al., 2020a). Future studies need to explore how desires to move/rest relate to dynamic changes in physical activity and sedentarism. Copyright © 2021 Stults-Kolehmainen, Blacutt, Fogelman, Gilson, Stanforth, Divin, Bartholomew, Filgueiras, McKee, Ash, Ciccolo, Brotnow Decker, Williamson and Sinha.
11 citations (Crossref) [2023-10-31] Place: Switzerland Stults-Kolehmainen, Matthew A. Digestive Health Multispecialty Clinic, Yale - New Haven Hospital, New Haven, CT, United States. Stults-Kolehmainen, Matthew A. Department of Biobehavioral Sciences, Teachers College, Columbia University, New York, NY, United States. Blacutt, Miguel. Department of Biobehavioral Sciences, Teachers College, Columbia University, New York, NY, United States. Fogelman, Nia. Yale Stress Center, Yale School of Medicine, New Haven, CT, United States. Gilson, Todd A. Department of Kinesiology and Physical Education, Northern Illinois University, DeKalb, IL, United States. Stanforth, Philip R. Department of Kinesiology and Health Education, The University of Texas at Austin, Austin, TX, United States. Divin, Amanda L. Department of Health and Human Performance, Northwestern State University, Natchitoches, LA, United States. Bartholomew, John B. Department of Kinesiology and Health Education, The University of Texas at Austin, Austin, TX, United States. Filgueiras, Alberto. Department of Cognition and Human Development, Rio de Janeiro State University, Rio de Janeiro, Brazil. McKee, Paul C. Department of Psychology, Southern Connecticut State University, New Haven, CT, United States. Ash, Garrett I. Pain, Research, Informatics, Medical Comorbidities and Education Center (PRIME), VA Connecticut Healthcare System, West Haven, CT, United States. Ash, Garrett I. Center for Medical Informatics, Yale School of Medicine, New Haven, CT, United States. Ciccolo, Joseph T. Department of Biobehavioral Sciences, Teachers College, Columbia University, New York, NY, United States. Brotnow Decker, Line. Yale Child Study Center, Yale School of Medicine, New Haven, CT, United States. Brotnow Decker, Line. Division of Mental Health, Akershus University Hospital, Lorenskog, Norway. Williamson, Susannah L. Department of Health and Kinesiology, Texas A&M University, College Station, TX, United States. Sinha, Rajita. Yale Stress Center, Yale School of Medicine, New Haven, CT, United States. Sinha, Rajita. Yale Child Study Center, Yale School of Medicine, New Haven, CT, United States.
Keywords: dept.psy; peer-reviewed

Testing Multiple Delivery Methods of the Virtual Exercise Games for Youth with T1D Peer Intervention: Protocol Development and Feasibility - Ash, Garrett I.; Nam, Soohyun; Mak, Selene S.; Stults-Kolehmainen, Matthew; Haughton, Adrian D.; Turek, Carolyn; Baker, Julien S.; Hieftje, Kimberly; Marks, Asher; Chmielewski, Annette; Shelver, Michael; Considine, Elizabeth G.; et al. (Hormone Research in Paediatrics, 2026)
Abstract – Introduction: Adolescents with type 1 diabetes (T1D) face barriers to moderate-to-vigorous physical activity (MVPA) such as uncertainty with self-management, limited access to supportive environments, and stigma related to living with diabetes. Opportunities for peer activities with T1D role model support are limited. To address this need, we tested iterative refinements of pilot Virtual Exercise Games for Youth with T1D (ExerT1D) for feasibility and acceptability. Methods: The program included 6 versions: study 1 (1.1–1.4) included an active video game, and study 2 (2.1–2.2) included a virtual reality (VR) active video game. All versions included T1D exercise management education by clinicians and goal-setting guided by young adult coaches with T1D. Results: Seventeen adolescents (median age 15.4 [IQR 14.6–16.4] years, 7 non-Hispanic white, 8 male, median HbA1c 8.1% [IQR 7.4%–11.1%]) were enrolled. Participants rated the program, comfort, clinicians, coaches, and group cohesion high/very high. Motivation for the video game was high. Building T1D and MVPA self-management skills was rated excellent at most sessions, as were peer interactions and enriched communication after adding immersive VR in study 2. Transitions between VR apps caused delays of 19 ± 6 min per 60 min–90 min session. Compared to baseline, HbA1c or glucose management indicator decreased over time in an exploratory analysis (d = −1.12, 90% CI: [−1.78, −0.48]). Conclusions: In a small cohort, the ExerT1D program facilitated a supportive environment for engaging diverse youth with T1D in an MVPA program led by T1D coaches. Larger studies are needed to assess the intervention’s impact on engagement with physical activity, glycemic outcomes, and quality of life. © 2026 S. Karger AG, Basel
Keywords: Diabetes; Peer support; Physical activity; Type 1; Video games; dept.hms

Urges to Move and Other Motivation States for Physical Activity in Clinical and Healthy Populations: A Scoping Review Protocol - Stults-Kolehmainen, Matthew A.; Blacutt, Miguel; Bartholomew, John B.; Boullosa, Daniel; Janata, Petr; Koo, Brian B.; McKee, Paul C.; Casper, Regina; Budnick, Christopher J.; Gilson, Todd A.; Blakemore, Rebekah L.; Filgueiras, Alberto; et al. (Frontiers in Psychology, 2022)
Motivation for bodily movement, physical activity and exercise varies from moment to moment. These motivation states may be “affectively-charged,” ranging from instances of lower tension (e.g., desires, wants) to higher tension (e.g., cravings and urges). Currently, it is not known how often these states have been investigated in clinical populations (e.g., eating disorders, exercise dependence/addiction, Restless Legs Syndrome, diabetes, obesity) vs. healthy populations (e.g., in studies of motor control; groove in music psychology). The objective of this scoping review protocol is to quantify the literature on motivation states, to determine what topical areas are represented in investigations of clinical and healthy populations, and to discover pertinent details, such as instrumentation, terminology, theories, and conceptual models, correlates and mechanisms of action. Iterative searches of scholarly databases will take place to determine which combination of search terms (e.g., “motivation states” and “physical activity”; “desire to be physically active,” etc.) captures the greatest number of relevant results. Studies will be included if motivation states for movement (e.g., desires, urges) are specifically measured or addressed. Studies will be excluded if referring to motivation as a trait. A charting data form was developed to scan all relevant documents for later data extraction. The primary outcome is simply the extent of the literature on the topic. Results will be stratified by population/condition. This scoping review will unify a diverse literature, which may result in the creation of unique models or paradigms that can be utilized to better understand motivation for bodily movement and exercise.
9 citations (Crossref) [2023-10-31]
Keywords: dept.psy; peer-reviewed

Establishing a global standard for wearable devices in sport and exercise medicine: Perspectives from academic and industry stakeholders - Ash, Garrett I.; Stults-Kolehmainen, Matthew; Busa, Michael A.; Gaffey, Allison E.; Angeloudis, Konstantinos; Muniz-Pardos, Borja; Gregory, Robert; Huggins, Robert A.; Redeker, Nancy S.; Weinzimer, Stuart A.; Grieco, Lauren A.; Lyden, Kate; et al. (Sports medicine (Auckland, N.Z.), 2021)
Millions of consumer sport and fitness wearables (CSFWs) are used worldwide, and millions of datapoints are generated by each device. Moreover, these numbers are rapidly growing, and they contain a heterogeneity of devices, data types, and contexts for data collection. Companies and consumers would benefit from guiding standards on device quality and data formats. To address this growing need, we convened a virtual panel of industry and academic stakeholders, and this manuscript summarizes the outcomes of the discussion. Our objectives were to identify (1) key facilitators of and barriers to participation by CSFW manufacturers in guiding standards and (2) stakeholder priorities. The venues were the Yale Center for Biomedical Data Science Digital Health Monthly Seminar Series (62 participants) and the New England Chapter of the American College of Sports Medicine Annual Meeting (59 participants). In the discussion, stakeholders outlined both facilitators of (e.g., commercial return on investment in device quality, lucrative research partnerships, and transparent and multilevel evaluation of device quality) and barriers (e.g., competitive advantage conflict, lack of flexibility in previously developed devices) to participation in guiding standards. There was general agreement to adopt Keadle et al.’s standard pathway for testing devices (i.e., benchtop, laboratory, field-based, implementation) without consensus on the prioritization of these steps. Overall, there was enthusiasm not to add prescriptive or regulatory steps, but instead create a networking hub that connects companies to consumers and researchers for flexible guidance navigating the heterogeneity, multi-tiered development, dynamicity, and nebulousness of the CSFW field. © 2021, The Author(s), under exclusive licence to Springer Nature Switzerland AG.
9 citations (Crossref) [2023-10-31] https://waseda.pure.elsevier.com/en/publications/establishing-a-global-standard-for-wearable-devices-in-sport-and- ; https://repository.up.ac.za/handle/2263/81930?show=full ; https://www.ncbi.nlm.nih.gov/pubmed/34468950 ; https://researchportal.northumbria.ac.uk/en/publications/establishing-a-global-standard-for-wearable-devices-in-sport-and- ; https://pubmed.ncbi.nlm.nih.gov/34468950/ ; https://link.springer.com/article/10.1007/s40279-021-01543-5
Keywords: Consensus; Exercise; Humans; Sports; Sports Medicine; United States; Wearable Electronic Devices; adult; article; consensus; consumer; data science; dept.hms; electronic device; exercise; female; human; human experiment; investment; major clinical study; male; sport; sports medicine